The Use of Politeness Strategies by Indonesian Vs Malaysian Student Debaters in the 2018 World Schools Debating Championship (WSDC) - Nurrahmah, Nurrahmah; Rukmini, Dwi; Yuliasri, Issy (English Education Journal, 2020)
The aims of this study were to analyze the types of politeness strategies realized by student debaters and how the Indonesian Vs Malaysian student debaters used politeness strategies in the debate competition. The data of this research were taken from youTube that video series of debate competition â€œWSDC 2018 R2: Indonesia VS Malaysia.â€ The study used a descriptive qualitative method which was analyzed using the politeness strategies propossed by (Brown and Levinson, 1987). The subjects in this study were 6 student debaters (2 teams) from Malaysia and Indonesia who participated in the 2018 World Schools Debating Championship (WSDC). This study found that most of the student debaters used positive politeness strategies to deliver their arguments appropriately. There were four types of politeness strategies realized by the debaters. Sub-strategies of positive politeness were mostly used by Indonesian debaters. They used sub-strategies of positive politeness to keep the hearer's positive face, to safe opinions when delivering arguments clearly as the opposition team and make the preposition team agreed with their insight. Malaysians used off-record strategy dominantly. They used inviting implicatures to imply meanings.